Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1002/(sici)1097-0320(19960315)26:1<32::aid-cyto5>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Quality control study by the French Cytometry Association on flow cytometric DNA content and S-phase fraction (S%)

Abstract: Clinical use of flow cytometric (FCM) DNA analysis requires effective quality controls. Thirty‐two laboratories with various degrees of FCM experience participated in the first phase of a quality control program organized by the Association Française de Cytométrie. All received diskettes containing ten list‐mode files and ten histogram files that were derived from FCM analysis of various unfixed tumor specimens. A total of 610 responses on DNA ploidy and cell cycle were obtained with three different DNA analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 2 publications
(4 reference statements)
0
15
0
Order By: Relevance
“…It has therefore been suggested that quality control programs should be performed in this field (2,19 -21). Attempts to improve the standardization have been done in our group, as well as in other groups (22)(23)(24)(25)(26)(27). These attempts have shown that it is logistically possible to organize a quality control program with many laboratories for standardizing DNA FCM analysis.…”
mentioning
confidence: 99%
“…It has therefore been suggested that quality control programs should be performed in this field (2,19 -21). Attempts to improve the standardization have been done in our group, as well as in other groups (22)(23)(24)(25)(26)(27). These attempts have shown that it is logistically possible to organize a quality control program with many laboratories for standardizing DNA FCM analysis.…”
mentioning
confidence: 99%
“…In the '90s, several EQA studies on DNA ploidy and Sphase assessment were undertaken (21)(22)(23). Jean Luc D'Hautcourt was also active in this application for many years.…”
mentioning
confidence: 99%
“…[1][2][3][4] Reproducible SPF results have been obtained by well-trained laboratories adhering to common recommendations. [5][6][7] Another approach for consideration of cell proliferation is the measurement of enzymes involved in DNA synthesis. For pyrimidine synthesis, two pathways have been identified.…”
mentioning
confidence: 99%